Performance evaluation of cogeneration plant at various turbine inlet temperatures - Veerabathini, Sumanraju; Sanke, Narsimhulu; Tinnavelli, Ramamohan Rao (Archives of Thermodynamics, 2026)
This experimental study examines the efficiencies of a cogeneration plant under various constant turbine inlet temperatures. The study considers the effects of changes in mass flow rate, inlet pressure, and inlet temperature on the electrical and overall efficiencies of the system. The findings indicate that the electrical and overall efficiencies are relatively consistent across different mass flow rates but vary slightly across different inlet pressures. The highest overall efficiency and electrical efficiency are obtained at a mass flow rate of 21.56 kg/s, an inlet pressure of 83 kG/cm², and an inlet temperature of 507°C. Under these operating conditions, the overall efficiency reached 58.06%, and the electrical efficiency was 26.26%. These findings suggest that the optimum operating conditions for this system depend on the specific requirements and priorities.